HUBUNGAN BUDAYA ORGANISASI DENGAN KINERJA PEGAWAI PADAKANTOR BADAN PENGENDALIAN DAMPAK LINGKUNGANDAERAH KOTA PADANG - REVA EKA PUTRI (Jurnal Bahana Manajemen Pendidikan, 2016)
The purpose of the research was to measure the correlation of workers performance with organization culture in Badan Pengendalian Dampak Lingkungan Daerah Kota Padang Office. Influences organization culture, one of them is raise workers performance. There are 45 workers being population in this research and 40 were taken as a sample. Using simple random sampling technique. The instrument used in this research is questionnaire. In general, the result of this research are (1) workers performance were right at 86,78%, (2) organization culture were right at 85%, (3) There is a significant correlation between organization culture with workers performance in Badan Pengendalian Dampak Lingkungan Daerah Kota Padang Office.